Targeted alpha therapy with the 224Ra/212Pb-TCMC-TP-3 dual alpha solution in a multicellular tumor spheroid model of osteosarcoma - Tornes, Anna Julie Kjøl; Stenberg, Vilde Yuli; Larsen, Roy Hartvig; Bruland, Øyvind Sverre; Revheim, Mona-Elisabeth; Juzeniene, Asta (Frontiers in Medicine, 2022)
Osteosarcoma patients with overt metastases at primary diagnosis have a 5-year survival rate of less than 20%. TP-3 is a murine IgG2b monoclonal antibody with high affinity for an epitope residing on the p80 osteosarcoma cell surface membrane antigen. The tumor-associated antigen p80 is overexpressed in osteosarcomas, and has very low normal tissue expression. We propose a novel dual alpha targeting solution containing two radionuclides from the same decay chain, including the bone-seeking 224Ra, and cancer cell-surface seeking 212Pb-TCMC-TP-3 for the treatment of osteoblastic bone cancers, circulating cancer cells and micrometastases. In this in vitro study, the cytotoxic effects of 212Pb-TCMC-TP-3 (single alpha solution) and 224Ra/212Pb-TCMC-TP-3 (dual alpha solution) were investigated in a multicellular spheroid model mimicking micrometastatic disease in osteosarcoma. OHS spheroids with diameters of 253 ± 98 μm treated with 4.5, 2.7, and 3.3 kBq/ml of 212Pb-TCMC-TP-3 for 1, 4, and 24 h, respectively, were disintegrated within 3 weeks. The 212Pb-TCMC-TP-3 induced a 7-fold delay in spheroid doubling time compared to a 28-times higher dose with the non-specific 212Pb-TCMC-rituximab. The 224Ra/212Pb-TCMC-TP-3 completely disintegrated spheroids with diameters of 218–476 μm within 3 and 2 weeks after 4 and 24 h incubation with 5 kBq/ml, respectively. Treatment with 1 kBq/ml of 224Ra/212Pb-TCMC-TP-3 for 24 h caused an 11.4-fold reduction in spheroid viability compared with unconjugated 224Ra/212Pb. The single and dual alpha solutions with TP-3 showed cytotoxicity in spheroids of clinically relevant size, which warrant further testing of the dual alpha solution using in vivo osteosarcoma models.